The complete chloroplast genome of a new candidate cultivar, Dae Ryun, of Abeliophyllum distichum Nakai (Oleaceae). Issue 2 (3rd July 2019) - Park, Jongsun; Min, Juhyeon; Kim, Yongsung; Xi, Hong; Kwon, Woochan; Jang, Taewon; Kim, Gwanho; Park, Jae-Ho
Abstract: To understand genetic features of new candidate cultivar, Dae Ryun of A. distichum, chloroplast genome was sequenced. Its length is 156, 019 bp and has four subregions: 86, 783 bp of large single-copy (LSC) and 17, 828 bp of small single-copy (SSC) regions are separated by 25, 704 bp of inverted repeat (IR) regions including 133 genes (87 protein-coding genes, 8 rRNAs, and 37 tRNAs). Overall GC content is 35.8%. Intraspecies sequence variations among four A. distichum chloroplast genomes present various numbers. Phylogenetic trees show that A. distichum is clustered with 12 Forsythia species.